Melatonin alleviates oxidative stress, inflammation, apoptosis, and DNA damage in acrylamide–induced nephrotoxicity in rats - Fatma Ibaokurgil; Hakan Aydin; Serkan Yildirim; Emin Sengul (Asian Pacific Journal of Tropical Biomedicine, 2023)
Objective: To investigate the effects of melatonin on renal inflammation, oxidative stress, apoptosis, as well as DNA and tissue damage in acrylamide-induced nephrotoxicity in rats. Methods: Fifty male rats were randomly divided into five groups. The control group received distilled water by gastric lavage for 11 days and the acrylamide group was administered acrylamide (50 mg/kg, i.g.) for 11 days. The MEL10+ACR and MEL20+ACR groups received intraperitoneal melatonin 10 and 20 mg/kg, respectively, for 11 days, and acrylamide (50 mg/kg, i.g.) was administered 1 h after melatonin injection. The MEL20 group was injected with melatonin (20 mg/kg) for 11 days. Kidney function tests were performed and biochemical and inflammatory parameters were determined. In addition, histopathological, immunohistochemical, and immunofluorescence examinationswerecarried out. Results: Melatonin significantly abated acrylamide-induced rise in serum urea and creatinine levels. Acrylamide caused oxidative stress, inflammation, apoptosis, as well as DNA and tissue damage in the kidneys. Melatonin treatment alleviated acrylamide-induced renal damage by exhibiting antioxidant, anti-inflammatory, and anti- apoptotic effects. Moreover, melatonin significantly ameliorated acrylamide-caused histopathological changes in kidney tissue. Conclusions: Melatonin attenuates acrylamide-induced renal oxidative stress, inflammation, apoptosis, and DNA damage in rats.